2009
DOI: 10.1590/s0101-20612009000100036
|View full text |Cite
|
Sign up to set email alerts
|

Secagem de fatias de abacaxi in natura e pré-desidratadas por imersão-impregnação: cinética e avaliação de modelos

Abstract: A demanda por alimentos processados que mantenham suas características as mais próximas possíveis dos produtos originais tem aumentado sensivelmente nas duas últimas dé-cadas. No que se refere ao processamento industrial, seja em grande ou pequena escala, há a necessidade de desenvolver tecnologias que contribuam para minimizar os efeitos adversos provocados nos alimentos pelo processamento, de forma a atender a crescente exigência por produtos de melhor qualidade por parte dos consumidores. Esse é o caso das … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
7

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 16 publications
0
6
0
7
Order By: Relevance
“…Several studies have focused on the use of these evaluation criteria, namely Dionello et al (2009) who studied models describing pineapple drying curves using R², SDR, and MAPE as selection criteria; Terra et al (2010) who applied R², SDR, and AIC as evaluation criteria to analyze the fitting of Gompertz and Logistic models to data of pygmy date palm fruits; Reis et al (2014) who studied clusters of garlic accessions, and concluded that, based on R², MSE, and MAD, the best-fitting model was the Logistic model; Lúcio et al (2015) who analyzed nonlinear models in the production of pumpkin and bell pepper using R²aj and standard error as evaluation criteria; and Deprá et al (2016) who evaluated logistic models for the growth of creole corn cultivars and of maternal half-sib progeny using R² and MAD to assess goodness of fit. Silveira et al (2012) reported that the greater the number of evaluation criteria applied, the more adequate is the indication of which are the bestfitting models.…”
Section: Traitsmentioning
confidence: 99%
“…Several studies have focused on the use of these evaluation criteria, namely Dionello et al (2009) who studied models describing pineapple drying curves using R², SDR, and MAPE as selection criteria; Terra et al (2010) who applied R², SDR, and AIC as evaluation criteria to analyze the fitting of Gompertz and Logistic models to data of pygmy date palm fruits; Reis et al (2014) who studied clusters of garlic accessions, and concluded that, based on R², MSE, and MAD, the best-fitting model was the Logistic model; Lúcio et al (2015) who analyzed nonlinear models in the production of pumpkin and bell pepper using R²aj and standard error as evaluation criteria; and Deprá et al (2016) who evaluated logistic models for the growth of creole corn cultivars and of maternal half-sib progeny using R² and MAD to assess goodness of fit. Silveira et al (2012) reported that the greater the number of evaluation criteria applied, the more adequate is the indication of which are the bestfitting models.…”
Section: Traitsmentioning
confidence: 99%
“…The authors attributed this result to the hardening of the surface layer of the fruit samples without osmotic pre-treatment, which prevented mass transport during drying (SANJINEZ-ARGANDOÑA et al, 2005). Dionello et al (2009) in the drying of pineapple slices verified a higher drying rate for the fresh fruit.…”
Section: Drying Kineticsmentioning
confidence: 72%
“…Com este tratamento preliminar, as características sensoriais (cor, sabor, textura) das frutas e hortaliças in natura são preservadas (SOUZA et al, 2009;PEREZ et al, 2013;SILVA et al, 2010c). Dionello et al (2009) também evidenciaram que o efeito do pré-tratamento osmótico sobre a taxa de secagem por convecção pode contribuir para melhores condições operacionais de conservação das frutas e hortaliças mediante a aplicação do sistema combinado (desidratação osmótica e secagem).…”
Section:  Por Osmoseunclassified